2017
DOI: 10.1177/1010428317706916
|View full text |Cite
|
Sign up to set email alerts
|

MiR-129-5p influences the progression of gastric cancer cells through interacting with SPOCK1

Abstract: The purpose of our study is to clarify the effect of microRNA-129-5p in the progression of human gastric cancer cells by regulating SPOCK1. The expression of microRNA-129-5p and SPOCK1 was tested by quantitative real-time polymerase chain reaction in tissues and cell lines. We validated the targeted relationship between microRNA-129-5p and SPOCK1 by dual luciferase reporter gene assay. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, colony formation, flow cytometry, transwell, and wound scratch a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…For example, mRNAs like miR‐105 and miR‐592 were reported to inhibit glioma cell malignancy, while some other mRNAs like miR‐21 and miR‐183 promoted the metastasis of glioma cells . Previous studies had revealed the suppressive role of miR‐129‐5p in several malignancies such as chondrosarcoma, gastric cancer and laryngeal cancer . In our study, we attempted to elucidate the biological function of miR‐129‐5p in human glioma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, mRNAs like miR‐105 and miR‐592 were reported to inhibit glioma cell malignancy, while some other mRNAs like miR‐21 and miR‐183 promoted the metastasis of glioma cells . Previous studies had revealed the suppressive role of miR‐129‐5p in several malignancies such as chondrosarcoma, gastric cancer and laryngeal cancer . In our study, we attempted to elucidate the biological function of miR‐129‐5p in human glioma.…”
Section: Discussionmentioning
confidence: 98%
“…22,23 Previous studies had revealed the suppressive role of miR-129-5p in several malignancies such as chondrosarcoma, gastric cancer and laryngeal cancer. [24][25][26] In our study, we attempted to elucidate the biological function of miR-129-5p in human glioma. We revealed the down-regulation of miR-129-5p in human glioma tissues and cells and the remarkable suppressive effects of miR-129-5p F I G U R E 7 TGIF2 inhibited cell apoptosis and blocked cell cycle of U87 and U251.…”
Section: Tgif2 Stimulated Glioma Cell Multiplication and Metastasismentioning
confidence: 99%
“…28 In gastric cancer, miR-129-5p could inhibit the expression of SPOCK1, leading to the suppression of cancer cell processes. 20 Nonetheless, the target relationship between SPOCK1…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miRNAs are widely dysregulated in GC tissues, 20 suggesting that miRNAs may play important roles in the development of GC. MiR‐129‐5p, the main functional executor of the miR‐129 family, is expressed at low levels in a variety of tumors and involves in cell proliferation, apoptosis, migration, and epithelial mesenchymal transition 21‐23 . It also play roles in the autophagy 24 and chemotherapy resistance 25 .…”
Section: Discussionmentioning
confidence: 99%